(untitled) (Perner’s Contacts, 2017)
This research aims to deliver a useful snapshot of current offering of Internet of Things (i4.0; IoT) functionality into strategic warehouse management products (WMS) in the environment of logistics and 3PL services providers. It also aims to map current demand and customer expectations, as well as customer preferences on functionalities available. In result, this paper aims to bring thoughts on next development and trends.